Phytochemical Screening and Evaluation of in Vitro Anti-Inflammatory Activity of Ethanolic Extract of Terminalia Mantaly H. perrier Leaves Using BSA Protein Denaturation Assay - Harfan, Anita Anida; Mulyani, Reni; Mulyadi, Dikdik (Jurnal Biologi Tropis, 2025)
The biological reaction to tissue damage known as inflammation is typified by the production of mediators including cytokines and prostaglandins. Long-term usage of non-steroidal anti-inflammatory medicines (NSAIDs) can have negative effects, despite their widespread use. This study explores the potential of Terminalia mantaly H. perrier (ketapang kencana), a plant known to contain various bioactive compounds, as a natural anti-inflammatory agent. The aim of this study was to analyze the phytochemical content and evaluate the anti-inflammatory activity of ethanol extracts of T. mantaly leaves using the Bovine Serum Albumin (BSA) protein denaturation method. 70% and 96% ethanol were used in the maceration process for extraction. The 70% ethanol extract included flavonoids, tannins, saponins, triterpenoids, terpenoids, and alkaloids, according to phytochemical screening. With an IC₅₀ value of 27,86 ppm Terminalia mantaly etanol extract 70%, the anti-inflammatory test revealed that the 70% ethanol extract at 400 ppm reduced protein denaturation by 92,29%, which was comparable to the inhibition by sodium diclofenac (84,04% at 50 ppm).  These results suggest that polar compounds in the 70% ethanol extract significantly contribute to its anti-inflammatory effect. Therefore, T. mantaly leaf extract demonstrates promising potential as a natural phytopharmaceutical candidate for inflammation therapy.